ABOUT SOME PROBLEMS OF STATE REGULATION OF THE INSTITUTE OF LAWYERS IN THE KYRGYZ REPUBLIC - Kurmanalieva A. A.; Shadybekov K. B.; Turatbekova Ch. A.; Sutalinova N. A. (Scientific Journal of Pedagogy and Economics, 2019)
The general characteristic of genesis and evolution of institute of legal profession in the Kyrgyz Republic, decentralization of the government, practice of application of conflict-of-laws rules and also humanity as principle of the law is presented in this article. The legal profession in the Kyrgyz Republic is the institute of civil society, protecting the rights and freedoms of the citizens, appeared in the framework of the criminal proceedings. Until current time this institute kept the independence of the state and law; was considered the most developed in the territory of the Post-Soviet states of Central Asia. Lawyers of the Kyrgyz Republic had considerable autonomy from executive power, were not under excessive guardianship of bodies of own self-government, possessed full legal practice, guarantees of the activity and could send their duties with relative professional and creative freedom. At the same time, the legal profession supposes the main functions, remained the organizational forms, and created in the old Soviet curves. Being the institute of official provision, the legal profession kept monopoly only for protection in criminal and administrative cases.